Types and Subtypes of the Posterior Part of the Cerebral arterial Circle in Human Adult Cadavers - Vasović, Ljiljana; Trandafilović, Milena; Jovanović, Ivan; Ugrenović, Slađana; Vlajković, Slobodan; Stojanović, Jovan (IntechOpen, 2011)
None